2009
DOI: 10.1007/s12598-009-0043-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrometallurgical purification of metallurgical grade silicon

Abstract: The effects of the particle size of ground metallurgical grade silicon (MG-Si), the sort of acids, and the type of stirring on the purified efficiency of MG-Si were investigated. It was found that a particle size less than 0.1 mm was most effective for acid leaching; the extraction yield of impurities was increased by 9% with HF leaching compared with HCl leaching and HNO 3 leaching, and increased by 7% with ultrasonic stirring compared with mechanical stirring. The principle of hydrometallurgical purification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 10 publications
2
34
2
Order By: Relevance
“…3a). A similar effect of particle size has been reported by Ma et al (2009), Yu et al (2007, Zhang et al (2009) andDietl (1983). They have shown that the metallic impurities precipitate at the grain boundaries and it is required to grind the MGSi to a size well below the grain diameter to expose the metallic impurities on the surface of the particles thus favoring effective contact with the lixiviant.…”
Section: Effect Of Particle Sizesupporting
confidence: 76%
See 3 more Smart Citations
“…3a). A similar effect of particle size has been reported by Ma et al (2009), Yu et al (2007, Zhang et al (2009) andDietl (1983). They have shown that the metallic impurities precipitate at the grain boundaries and it is required to grind the MGSi to a size well below the grain diameter to expose the metallic impurities on the surface of the particles thus favoring effective contact with the lixiviant.…”
Section: Effect Of Particle Sizesupporting
confidence: 76%
“…For the removal of Fe and Ti from such alloy phases it is required to leach the MGSi with hydrofluoric acid (Santos et al, 1990). Despite our findings and those of Ma et al (2009), Santos et al (1990 were successful in removing~50% Al, 80% Fe, 25% Ca and 98% Ti by treating MGSi with 2 M HCl at 50°C for 8 h, which is a relatively mild condition as compared to the present investigation. However, these authors did not report the nature of the Fe and Ti alloy phases present in their MGSi samples.…”
Section: Microstructure Of Silicon Before and After Purificationcontrasting
confidence: 69%
See 2 more Smart Citations
“…Margarido et al made a dynamic mechanism analysis for the Fe-Si alloy on the refining under acid leaching route and pointed out that the acid leaching process conformed to the cracking shrinking model controlled by chemical reaction [10][11]. Ma et al pointed out that the extraction yield of impurities increased by 9 % with HF leaching more than with HCl and nitric acid (HNO 3 ) in the leaching of MG-Si [12].…”
Section: Introductionmentioning
confidence: 99%